The usage of the railroad terminal resources - Jarašūniene, Aldona (Transport, 2004)
With the growth of freight transportation by rail the main attention should be focused on the function of railway terminal activities and optimization, where the arriving trains are disbanded and new trains are arranged according to the train formation plan A loading process is analyzed. Functional structure of terminals is defined by a technological process. The dynamic tasks of management of trains flows are formulated. The efficiency of railway terminal activities should depend on the optimization of the process of growth of freight transportation.First Published Online: 27 Oct 2010